Vector competence of the African argasid tick Ornithodoros moubata for the Q fever agent Coxiella burnetii. - Marie Buysse; Maxime Duhayon; Franck Cantet; Matteo Bonazzi; Olivier Duron (Public Library of Science (PLoS), 2021)
Q fever is a widespread zoonotic disease caused by the intracellular bacterium Coxiella burnetii. While transmission is primarily but not exclusively airborne, ticks are usually thought to act as vectors on the basis of early microscopy studies. However, recent observations revealed that endosymbionts of ticks have been commonly misidentified as C. burnetii, calling the importance of tick-borne transmission into question. In this study, we re-evaluated the vector competence of the African soft tick Ornithodoros moubata for an avirulent strain of C. burnetii. To this end, we used an artificial feeding system to initiate infection of ticks, specific molecular tools to monitor further infections, and culture assays in axenic and cell media to check for the viability of C. burnetii excreted by ticks. We observed typical traits associated with vector competence: The exposure to an infected blood meal resulted in viable and persistent infections in ticks, trans-stadial transmissions of infection from nymphs to adults and the ability of adult ticks to transmit infectious C. burnetii. However, in contrast to early studies, we found that infection differed substantially between tick organs. In addition, while adult female ticks were infected, we did not observe C. burnetii in eggs, suggesting that transovarial transmission is not effective. Finally, we detected only a sporadic presence of C. burnetii DNA in tick faeces, but no living bacterium was further isolated in culture assays, suggesting that excretion in faeces is not a common mode of transmission in O. moubata.